2011
DOI: 10.3892/or.2011.1559
|View full text |Cite
|
Sign up to set email alerts
|

EGFR mutations predict a favorable outcome for malignant pleural effusion of lung adenocarcinoma with Tarceva therapy

Abstract: Abstract. The aim of the present study was to evaluate the therapeutic effects and adverse reactions of Tarceva treatment for malignant pleural effusion (MPE) caused by metastatic lung adenocarcinomas. One hundred and twenty-eight patients who failed first-line chemotherapy drug treatment were divided into a mutation and a non-mutation group according to the presence or absence of epidermal growth factor receptor (EGFR) mutations. Each patient received closed drainage combined with simple negative pressure suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The detached tumor cells, individually or in small clusters, are uniquely capable of proliferating and growing, despite their presumably unfavorable locale [24]. The effusions offer a premetastatic niche, which functions as a dynamic reservoir that can supply the cancer tissue through autocrine and/or paracrine interactions with growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…The detached tumor cells, individually or in small clusters, are uniquely capable of proliferating and growing, despite their presumably unfavorable locale [24]. The effusions offer a premetastatic niche, which functions as a dynamic reservoir that can supply the cancer tissue through autocrine and/or paracrine interactions with growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports [ 33 , 37 ] found that overall survival (OS) could be prolonged in EGFR positive ADC patients with MPE undergoing EGFR -TKI therapy. Meanwhile, several retrospective studies [ 33 , 34 ] discovered that patients with ADC and MPE had a higher rate of EGFR mutation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the patients who were treated with EGFR-TKIs were mostly never smokers or light smokers and had no underlying lung diseases, highlighting the potential risk of combining EGFR-TKI therapy and pleurodesis. Considering the effectiveness of EGFR-TKIs in the treatment of EGFR-mutant lung cancer, including patients with MPE ( 12 ), EGFR-TKI therapy alone (without pleurodesis), seems be a preferable treatment option for reducing the risk of ILD. It is now widely accepted that EGFR-TKI alone (without pleurodesis) can prevent the recurrence of MPE ( 13 ).…”
Section: Discussionmentioning
confidence: 99%